2016
DOI: 10.1186/s12872-016-0189-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of coronary artery disease and its risk factors in Kerala, South India: a community-based cross-sectional study

Abstract: BackgroundThere are no recent data on prevalence of coronary artery disease (CAD) in Indians. The last community based study from Kerala, the most advanced Indian state in epidemiological transition, was in 1993 that reported 1.4 % definite CAD prevalence. We studied the prevalence of CAD and its risk factors among adults in Kerala.MethodsIn a community-based cross sectional study, we selected 5167 adults (mean age 51 years, men 40.1 %) using a multistage cluster sampling method. Information on socio-demograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
91
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 23 publications
7
91
4
Order By: Relevance
“…Gender and past history were significant predictors of CAD. These findings are consistence with findings of other studies done in Sri Lanka and in the region [13,14,15,16,17].…”
Section: Papersupporting
confidence: 77%
See 1 more Smart Citation
“…Gender and past history were significant predictors of CAD. These findings are consistence with findings of other studies done in Sri Lanka and in the region [13,14,15,16,17].…”
Section: Papersupporting
confidence: 77%
“…A similar study was done in India using RAQ and Minnesota ECG coding. In this study, crude and age adjusted prevalence of CAD was reported as 5.8% and 3.8% respectively [17].…”
Section: Introductionmentioning
confidence: 99%
“…25.2% of the rural population of central India smoked as in study done by Patil S.S et al 33 Smoking was also less predominant (7.5%) in urban population of study subjects in a study done by Walia R et al 30 Krishnan M.N. et al 29 documented 33.42% smokers of which 28% was prevalent in males. This high percentage of smoking as reported in our study could be due to local rural traditions of hookah smoking and majority of study population being from rural area.…”
Section: Discussionmentioning
confidence: 85%
“…Atleast checking of blood sugars should be done atleast for first 6 months at every follow up after the acute coronary event so as to pick up any revealing latent new onset diabetes thus preventing morbidity and mortality arising out of it or its consequences. In a study conducted to find NOD after renal transplant in 2014 founded that the need for more aggressive DM treatment (suggesting a worsening of DM status) was most usually seen between discharge and 3 months; 50% of patients with preexisting DM required more aggressive DM treatment post-transplantation (X3(2) = 13.25; P = .001) [10,11,12] . This study supports our finding relative rapid onset of Diabetes in predisposed individual.…”
Section: Resultsmentioning
confidence: 99%